Tubercular parotitis; a forgotten entity - Bhattacharya, Gourav; Khadanga, Sagar; Dugar, Dharmendra; Kumar Thatoi, Pravat; Prasad Satapathy, Shakti (International Journal of Medical Research and Review, 2016)
Tubercular parotitis is extremely rare, even in countries such as India, where the burden of tuberculosis is very high. Clinically, it presents as a slow-growing localized mass, indistinguishable from a neoplasm. Imaging studies are non-specific. USG guided fine needle aspiration cytology (FNAC) can provide a pre operative screening procedure. We present a case of parotid tuberculosis in a 56-year-old diabetic male with short duration of fever and parotitis. We diagnosed the case on the basis of high erythrocyte sedimentation rate, lymphocyte predominant parotitis, epithelioid granuloma in right pre auricular lymphnode and parotid aspirate polymerase chain reaction (PCR) yielding mycobacterium tuberculosis. The patient responded well to 6 months of anti tubercular therapy with optimized diabetes and hypertension management and doing well at the end of 1 year of completion of treatment.